Oral supplementation with selected Lactobacillus acidophilus triggers IL-17-dependent innate defense response, activation of innate lymphoid cells type 3 and improves colitis - Hrdý, Jiří; Couturier-Maillard, Aurélie; Boutillier, Denise; Lapadatescu, Carmen; Blanc, Philippe; Procházka, Jan; Pot, Bruno; Ryffel, Bernhard; Grangette, Corinne; Chamaillard, Mathias (Scientific reports, 2022)
Live biotherapeutic products constitute an emerging therapeutic approach to prevent or treat inflammatory bowel diseases. Lactobacillus acidophilus is a constituent of the human microbiota with probiotic potential, that is illustrated by improvement of intestinal inflammation and antimicrobial activity against several pathogens. In this study, we evaluated the immunomodulatory properties of the L. acidophilus strain BIO5768 at steady state and upon acute inflammation. Supplementation of naïve mice with BIO5768 heightened the transcript level of some IL-17 target genes encoding for protein with microbicidal activity independently of NOD2 signaling. Of these, the BIO5768-induced expression of Angiogenin-4 was blunted in monocolonized mice that are deficient for the receptor of IL-17 (but not for NOD2). Interestingly, priming of bone marrow derived dendritic cells by BIO5768 enhanced their ability to support the secretion of IL-17 by CD4+ T cells. Equally of importance, the production of IL-22 by type 3 innate lymphoid cells is concomitantly heightened in response to BIO5768. When administered alone or in combination with Bifidobacterium animalis spp. lactis BIO5764 and Limosilactobacillus reuteri, BIO5768 was able to alleviate at least partially intestinal inflammation induced by Citrobacter rodentium infection. Furthermore, BIO5768 was also able to improve colitis induced by 2,4,6-trinitrobenzene sulfonic acid (TNBS). In conclusion, we identify a new potential probiotic strain for the management of inflammatory bowel diseases, and provide some insights into its IL-17-dependent and independent mode of action.
Keywords: idiopatické střevní záněty; Inflammation; kyselina trinitrobenzensulfonová; Trinitrobenzenesulfonic Acid; Lymphocytes; kolitida; Bifidobacterium animalis; Immunity, Innate; Interleukin-17; zánět; Lactobacillus acidophilus; lymfocyty; Mice; probiotika; enterobakteriální infekce; Probiotics; přirozená imunita; zvířata; Enterobacteriaceae Infections; interleukin-17; myši; Colitis; Inflammatory Bowel Diseases; Animals